A descriptive study to assess the knowledge regarding menstrual problems and their management among adolescent girls in selected institute of Dehradun, Uttarakhand - Rawat, Shivani; Karmiyal, Nikita; Chauhan, Ekta; Saini, Simran; Kothiyal, Deepti; Karna, Vaibhav; Rana, Divyanshi; Praveen, Shama; Pundir, Namrata; Kumar, Chandan (International Journal Of Community Medicine And Public Health, 2025)
Background: Menstrual problems are a disruptive physical and/or emotional symptoms just before and during menstruation, including heavy bleeding, missed periods and unmanageable mood swings. Menstrual problems can be cause of significant amount of stress to both the adolescent girls and their parents. Appropriate and early management of patient is necessary in order to minimize the possibility of complications in future. Methods: Quantitative research approach with non-experimental descriptive research design was used in the present study. A total of 61 samples were selected through non probability convenient sampling technique from adolescent girls of radiant public school, Doiwala, Dehradun. Structured knowledge questionnaire was given to the participants and data was collected in order to assess knowledge of each participant. Results: The present study showed that out 61 adolescent girls 95% (58) adolescents were suffering from dysmenorrhea during menstruation and 62.3% of adolescent girls had excellent knowledge regarding menstrual problems. There was a significant association between level of knowledge with age group and body type. Conclusions: From the findings of the study, it was concluded that out of 61 adolescent girls 95% (58) were suffering from dysmenorrhea during menstruation and about 62.3% have excellent knowledge regarding menstrual problems and 93.44 adolescent girls uses hot water bag to manage dysmenorrhea.